2018
DOI: 10.1136/vr.104414
|View full text |Cite
|
Sign up to set email alerts
|

PDGFR‐α, PDGFR‐β, VEGFR‐2 and CD117 expression in canine mammary tumours and evaluation of the in vitro effects of toceranib phosphate in neoplastic mammary cell lines

Abstract: Canine mammary tumours (CMTs) are one of the most common malignancies in bitches. Platelet-derived growth factor receptor (PDGFR) α and β, vascular endothelial growth factor receptor-2 (VEGFR-2) and CD117 are tyrosine kinase receptors involved in several tumours and represent suitable targets for specific therapy with toceranib phosphate. The purpose of this study was to evaluate the expression of these receptors in the pathogenesis and progression of CMTs. PDGFRα, PDGFRβ, VEGFR-2 and CD117 were expressed in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…All of them showed a heterogeneous amount of mRNA, indicating cell‐line specific gene expression. Interestingly, similar variations were previously described when considering protein levels …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…All of them showed a heterogeneous amount of mRNA, indicating cell‐line specific gene expression. Interestingly, similar variations were previously described when considering protein levels …”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, similar variations were previously described when considering protein levels. 6,7,33 Cell lines were further investigated with several biological assays to determine whether cell migration was affected by treatment with TOC. Transwell assays demonstrated that all OSA cell lines were able to migrate in the absence of chemo-attractive factors; conversely, Overall, these in vitro results suggested that Wall and Penny cells responded to TOC treatment mainly by reducing invasion rather than proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal and hyperplastic mammary tissues show a moderate to strong diffusely cytoplasmic and membranous c-Kit positivity even though the relationship between the tumour histotype and the presence or absence of -c-Kit expression is still debated. Recently published studies have demonstrated a decrease in c-KIT expression in benign tumours as well as in the tubulopapillary carcinoma; no c-KIT expression is reported in high-grade carcinoma, although a cytoplasmic expression pattern could partially increase cellular proliferation (Brunetti et al, 2014;Gattino et al, 2018;Morini et al, 2004). This case report aims to add an extra contribution to the Veterinary Medicine literature on collision tumours.…”
Section: Discussionmentioning
confidence: 82%
“…The rabbit polyclonal anti‐VEGFR‐2 antibody was previously confirmed to cross‐react with the canine tissue samples by Western blotting and immunohistochemistry 16 and the information about the cluster of differentiation 31 (CD31) antibody cross‐reactivity was provided by the manufacturer (Thermo Fisher Scientific). In this study, the VEGF‐A cross‐reactivity in dogs was evaluated by Western blotting, following the procedures described by Rivera‐Calderón et al 17 Briefly, four canine normal frozen tissues were mechanically homogenized and protein extraction was performed using the radioimmunoprecipitation assay buffer.…”
Section: Methodsmentioning
confidence: 99%